ANALISIS LANDASAN FILOSOFIS, SOSIOLOGIS, DAN YURIDIS PEMBENTUKAN PERATURAN DAERAH RP3KP DI KABUPATEN MANGGARAI - Kurniawan Geong, Mario Pietro; Tasya Oeleu, Theofilla; N. Lobo, Ferdinandus (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The development of housing and residential areas in Manggarai Regency is a strategic basic need in shaping the nation’s character and identity. This document analyzes the urgency of forming Regional Regulations on Development and Housing Plans and Settlement Areas (RK3KP) based on three main pillars: philosophical, sociological and juridical. The philosophical basis emphasizes the importance of local values ??and social justice in development policies, while the sociological basis highlights the active participation of the community in every planning stage to ensure relevant and harmonious policies. On the other hand, the juridical basis provides legal certainty and accountability in the planning and implementation process. By considering socio-economic and environmental challenges, this document emphasizes that the integration of environmentally friendly and sustainable development principles is very important to create residential areas that are livable and safe for future generations. Through this in-depth study, it is hoped that the formation of effective and implementable regulations can be realized, supporting sustainable and equitable regional development.